Pirates of the Caribbean: the curse of the black pearl - Verbinski, Gore 1964-; Elliott, Ted 1961-; Depp, Johnny 1963-; Rush, Geoffrey 1951-; Bloom, Orlando 1977- (Walt Disney Home Entertainment, 2003)
The roguish yet charming Captain Jack Sparrow's idyllic pirate life capsizes after his nemesis, the wily Captain Barbossa, steals his ship the Black Pearl and later attacks the town of Port Royal. Captain Barbossa kidnaps the governor's beautiful daughter, Elizabeth. In a gallant attempt to rescue her and recapture the Black Pearl, Elizabeth's childhood friend Will Turner joins forces with Jack. What Will doesn't know is that a cursed treasure has doomed Barbossa and his crew to live forever as the undead.
Keywords: Adventure and adventurers -- Drama; Pirates -- Drama; Sailing ships -- Drama; Film; Feature films